PENGEMBANGAN BUKU PANDUAN BIMBINGAN KELOMPOK TEKNIK SOSIODRAMA UNTUK MENGURANG PERILAKU AGRESIF VERBAL SISWA SMP - Lailatul Mukarromah; Dewi Masyitoh; Ade Irma Noviyanti (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
Among an attempt to lessen verbally hostile behavior among junior high school pupils, this study intends to create a manual for group supervision that uses sociodrama approaches. One of the issues that interferes with students' social interactions and learning process is verbally abusive behavior. For group guidance services to address this issue, guidance and counseling teachers require efficient and organized media. In order to reduce verbally aggressive behavior in junior high school students, research and development (RD) with a procedural development model is employed. This model adapts the strategy from Borg and Gall and includes the following steps: (1) preliminary study and data collection, (2) planning, (3) initial product development, (4) product testing, and (5) sociodrama guide. The created product was tested on students and verified by media specialists, material specialists, and potential users (counselors). The total product development is in the good category, according to the findings of the material specialists. The media specialists' findings are classified as extremely good. The outcomes of potential consumers are in the very good range. Additionally, the small group test's findings are classified as very good. These findings suggest that the product development can serve as a guide for using sociodrama to help junior high school students behave less aggressively when speaking.